2008
DOI: 10.1088/0022-3727/41/12/125306
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of resonance frequency change induced by adsorption

Abstract: Microcantilever-based techniques can be used to explore the autonomy and property of molecules (e.g. DNA and single actin filaments) adsorbed on a surface. A theoretical model is presented here to predict the resonance frequency of a cantilever induced by physically adsorbed atoms/molecules. The cantilever is modelled as a sandwich beam containing two surface layers of a finite thickness and a bulk layer between them. It is found that the resonance frequency shift depends sensitively on both the mass and bendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…16) There is no damping in equations (2.7) and (2.12), which is also the case in many studies [3,4,6,7,13,18,19,33]. The presence of damping reduces the resonance, and damping can be determined by the so-called half-power method from the frequency response curve obtained by experiment [45].…”
Section: Model Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…16) There is no damping in equations (2.7) and (2.12), which is also the case in many studies [3,4,6,7,13,18,19,33]. The presence of damping reduces the resonance, and damping can be determined by the so-called half-power method from the frequency response curve obtained by experiment [45].…”
Section: Model Developmentmentioning
confidence: 99%
“…The application of the ansatz that nanostructure = bulk + surface [1] in continuum mechanics leads to the so-called core-shell model [2][3][4][5][6][7][8][9][10][11], in which the core is the bulk and the shell is the surface layer. In a surface layer, the total surface stress (τ ) is given as follows [2,4,5,[8][9][10][11][12][13]: 1) where is the dimensionless strain and C s is the surface modulus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hagan et al [15] presented a model to evaluate the beam deflections induced by adsorption and subsequent hybridization of DNA molecules and concluded that the dominant contribution to the deflection arises from hydration forces, instead of conformational entropy or electrostatics. Recently Zhang et al considered the effects of adsorption on the resonance frequency change and bending of microcantilever by adopting the EulereBernoulli beam model [16,17].…”
Section: Introductionmentioning
confidence: 99%